A Study of Distribution Problems Based on Express Transportation Networks - Deng, Lige (Transactions on Computer Science and Intelligent Systems Research, 2024)
This article uses the distribution data of rookie stations in Jinan City to explore the allocation problem of express delivery transportation networks. Firstly, in response to the uneven spatial layout of rookie Station, a corresponding evaluation index system was established based on K-means and TOPSIS models. The results showed that rookie Station exhibited characteristics of agglomeration in the central urban area and dispersion in the remote urban area. Secondly, by establishing a Floyd model to plan the route, the most reasonable transfer center was determined, and the results showed that the Shizhong District was the most suitable transfer station for Jinan City, while Zhangqiu District was selected as the second transfer station. Finally, based on the population density and express delivery demand in Jinan City, a model for express delivery allocation business points was established, and the optimal solutions for express delivery allocation business points in each district were obtained.